Melampaui Batas (Noodewwr Exces) dalam Membela Diri; Studi Perbandingan Antara Hukum Pidana Islam dan Hukum Positif - Haq, Islamul; Wahidin, Wahidin; Saidah, Saidah (Universitas Islam Negeri Alauddin Makassar, 2020)
One form of action that gets criminal abolition is an action taken by someone in order to defend themselves from an emergency threat, but the act of self-defense sometimes exceeds the proper limit. This study aims to find out how the comparison between Islamic criminal law and positive law towards actions that exceed the limits (noodweer exces) in self-defense. This research is a qualitative research study using library research. According to the results of this study, it was found that the defense carried out beyond the limit (Noodweer exces), in positive law as stipulated in KUHP 49 paragraph 2, when self-defense that exceeds the limit carried out under conditions of